1997
DOI: 10.1111/1467-8608.00063
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Consumerism: The Case Of “Fairly–Traded” Coffee

Abstract: Consumer concern for “ethical products”, or ethical aspects of the goods which they purchase, is a subject of increasing interest and research,which is here illustrated by an examination of the Fair Trade movement, with special reference to coffee as an indicative commodity. Kate Bird, is currently Lecturer in the Development Administration Group, School of Public Policy, Birmingham University, Birmingham B15 2TT, England, having previously worked abroad and written her MSc dissertation at Wye College on fair … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
78
1
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(83 citation statements)
references
References 1 publication
2
78
1
2
Order By: Relevance
“…Many papers on fair trade are normative (Moore, 2004;Reynolds, 2002;McDonagh, 2002) and the few which are empirical cover a range of topics from outside of the organisational context, for example Strong (1996Strong ( , 1997 and Bird and Hughes (1997).…”
Section: Methodsmentioning
confidence: 99%
“…Many papers on fair trade are normative (Moore, 2004;Reynolds, 2002;McDonagh, 2002) and the few which are empirical cover a range of topics from outside of the organisational context, for example Strong (1996Strong ( , 1997 and Bird and Hughes (1997).…”
Section: Methodsmentioning
confidence: 99%
“…Key demographic factors highlighted across the segmentation strand of literature include income, gender, age and level of education. However, age (Bird and Hughes, 1997, Nicholls and Opal, 2008, Context Marketing, 2010 and income (De Peslmacker, et al, 2005 andTNS CAPI, 2009) were the most common factors found to influence shopper preference and attitudes towards fairtrade products.…”
Section: Fairtrade Shopper Segmentationmentioning
confidence: 99%
“…Previous studies have used various forms and combinations of life-stage and geo-demographic factors as distinguishing features for fairtrade shopper segmentation (Bird and Hughes, 1997, Moore, 2004and Fairtrade Foundation/MORI, 2004, Nicholls and Opal, 2008, TNS CAPI, 2009and Globescan, 2009). Actual shopper data (loyalty card) used for this research covers both life-stage and lifestyle segmentations.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Furthermore, in the coffee industry, the multinational Nestlé has introduced the brand Partner Blend, which only requires a small percentage of the production process to be carried out within some organic guidelines. Given this proliferation of declarations, ratings, certifications and labels, many analysts believe that one of the main challenges to the survival of FT is the recognition of its distinctive label (Bird and Hughes, 1997;Davies and Crane, 2003;Melo and Wolf, 2005;Moore, 2004;Renard, 2003).…”
mentioning
confidence: 99%